Improving Students Learning Activeness in Social Studies Subjects through Student Teams Achievement Division (STAD) Cooperative Learning Model - Rohman, Farrij Andika; Imam Khairi, Ahmad; Devi, Bernadetta (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2024)
This research is motivated by the problems found in class VII E at SMPN 2 Pamekasan, namely the low level of student learning activeness in social studies lessons, in the classroom the teacher still uses the lecture method in explaining the learning material and continued with practice questions, as a result learning activities become unvaried and limited. cooperative learning model type Student Teams Achivement Division (STAD) is used to increase student activeness. This research used classroom action research (PTK) which was carried out in two cycles, each cycle consisting of four stages, namely the planning, implementation, observation, and reflection stages. The subjects of this study were students of class VII E consisting of 32 students. The research instruments used in this study were observation guidelines for student learning activeness, and field notes. While the data collection techniques used in this research are participatory observation, interviews, and documentation. The data analysis used is qualitative data analysis, which consists of data reduction, data presentation, and conclusion drawing, and quantitative data analysis with a percentage of the assessment of student learning activeness in the application of the Student Teams Achivement Division (STAD) type cooperative learning model. Based on the results of the study it can be concluded that there is an increase in student learning activeness in social studies learning from cycle I to cycle II. Indicators pay attention to the teacher’s explanation increased 12.51% from cycle I to cycle II. Indicators record or summarize the subject matter increased 28.13% from cycle I to cycle II. Indicators asking questions to teachers or friends experienced an increase of 26.57% from cycle I to cycle II. Indicators answering questions from teachers or friends increased 39.06% from cycle I to cycle II. Indicators discussing with group members in solving problems increased 21.88% from cycle I to cycle II. Indicators helping fellow group members in understanding the subject matter increased 14.07% from cycle I to cycle II. The indicator of doing tasks given by the teacher increased 28.12% from cycle I to cycle II. The indicator of doing quizzes individually increased 39.06% from cycle I to cycle II. And student learning activeness showed a score of 93.75% at the end of the cycle.